Workof artistsis in the a esthetic problems of visual culture of Ukraine - O. L. Khramova-Baranova; I. F. Saenko (History of science and technology, 2016)
A question of national consciousnessisone of topicaland his decision is impossible without the study of history of material and spiritual culture of our country. National style characterizesthe artistic phenomenaof folk and professiona lart, and work of artistshas a ponderablevalue and cantheaesthetic aspects of questions of visual culture of Ukraine.